The case for formal visual literacy teaching in higher education - Jordaan, Christina; Jordaan, Danie (South African Journal of Higher Education, 2016)
Abstract Visual literacy is crucially important in a contemporary society dominated by visual media, yet visual literacy teaching and education has not (yet) achieved sufficient recognition in terms of tertiary education curricula. One criticism against the use of social media technologies is the perceived inability of participants to distinguish between virtual and real worlds. This is the result of an education system that has not given adequate prominence to the development of critical visual literacy, but assumes that students will “pick up” the necessary competencies along the way. The answer is not to try and resist the new paradigm of a mediated society where the virtual has increasingly taken the place of face-to-face human interaction, but to explore visual technologies in order to design subject-specific taxonomies of learning and appropriate methodologies for the teaching of visual semiotics. In this study poster elicitation was used to analyse data on visual literacy. The data were obtained from narratives written by 89 respondents after studying two posters about visual messaging. The data revealed that visual images do not constitute a universally understandable means of communication that function independently of language. Keywords: Visual literacy in teaching, social media training, mediated society, visual semiotics in education, university curricula.